Factors associated with parental stress among mothers of school-age children in rural Bangladesh - Yorin Watabe; Syed Emdadul Haque; Benay Kumar Datta; Abul Kashem; Minato Nakazawa; Ruoyan Gai Tobe; Rintaro Mori (Journal of Public Health and Development, 2026)
Given the paucity of studies on parental stress among mothers with school-age children in low- and middle-income countries (LMICs), this study examined the association between maternal parental stress and child characteristics including behavioral and psychosocial difficulties and growth status in rural Bangladesh. A total of 617 mother–child dyads were recruited and interviewed using structured questionnaires in Lohagora Upazila, Narail District, Bangladesh. Maternal stress was measured with the Parental Stress Scale (PSS). Multiple linear regression analysis was performed to understand the relationship between the PSS scores and children’s factors including Strength and Difficulties Questionnaire (SDQ)-Total Difficulties Score (TDS), growth status and gender. The analyzed covariates included the mothers’ socio-demographics and distribution of the maternal and child health (MCH) handbook. Results showed that higher SDQ-TDS and stunting were significantly associated with higher maternal parental stress. Distribution of the MCH handbook had a modifying effect on the SDQ-TDS factors. In subgroup analysis of a multiple regression model, the partial regression coefficient of SDQ-TDS was 0.308 (p